Look- n-Learn: Our universe - Young learner (New Delhi : Young learner publications, 2020)
Look-n-Learn is a series of eight books imparting basic but important information on various subjects. The books have been prepared keeping in mind the tenderness and the reading level of young minds. The age-appropriate content provides relevant information in an interesting and easy-to-learn manner. The books are an essential means to enable the children to think beyond the box
Location: 4C
Keywords: Book